Pengaruh Kualitas Pelayanan, Harga, dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Jasa Transportasi (Gojek) di Kota Padang - Valendra Valendra; Sophan Sophian (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the relationship between service quality, price, and customer satisfaction with Gojek transportation service loyalty. This study is quantitative in nature, with online motorcycle taxi (Gojek) users as the research subjects. This study uses a quantitative method with a non-probability sampling technique and accidental sampling technique with a sample size of 85 samples. Data analysis was performed using multiple linear regression with the SPSS program. The results showed that service quality had a positive and significant effect on customer loyalty, thus accepting the first hypothesis (H1). The price factor was also proven to have a positive and significant effect on increasing customer loyalty, thus accepting the second hypothesis (H2). Meanwhile, customer satisfaction did not have a significant effect on customer loyalty, so the third hypothesis (H3) was rejected. These findings indicate that customer loyalty to Gojek services in Padang City is more influenced by service quality and price suitability, while customer satisfaction is not yet strong enough to encourage loyalty.